Characterization and Valorization of 'Sulmona Red Garlic' Peels and Small Bulbs - Alba Lasalvia; Francesco Cairone; Stefania Cesa; Alessandro Maccelli; Maria Elisa Crestoni; Luigi Menghini; Simone Carradori; Beatrice Marinacci; Marialucia Gallorini; Osama Elsallabi; Mirko Pesce; Antonia Patruno (MDPI AG, 2022)
'Sulmona red garlic' is an Italian variety characterized by a red tunica surrounding a white bulb. Red tunicae and non-commercial small bulbs are food wastes that must be studied for their added value. Hydroalcoholic extracts, obtained by separated inner and outer tunicae and peeled bulbs of small commercial 'Sulmona red garlic' bulbs, harvested at two different years, were first characterized with respect to their color, polyphenolic content, and antiradical activity. Then, an untargeted metabolic profile by means of electrospray ionization Fourier transform ion cyclotron resonance (ESI FT-ICR) mass spectrometry led to a comparative evaluation of the chemical diversity of six different samples. The study was completed by biological tests aiming to evaluate the associated health potential. Data on monocytes/macrophages showed good biocompatibility and a promising cytoprotective effect under oxidative stress conditions of all the extracts. At a molecular level, all the garlic extracts were able to downregulate the hydrogen peroxide-induced cyclooxygenase-2 and inducible nitric oxide synthase expression through the modulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-ĸB) and peroxynitrite intracellular amounts, at different extents depending on the extract, the cell type, and the concentration. On the whole, data highlight an associated health potential of the extracts of this waste plant material both in terms of cytoprotection and of anti-inflammatory activity.